Trade unions and the gender wage gap: Evidence from China - Xinxin Ma; Peng Zhan (Journal of Applied Economics, 2024)
While it is assumed that trade unions may influence the gender wage gap, evidence is scarce on this issue. This study investigates the issue in China using national longitudinal survey data from 2010 to 2020. The results reveal that the union wage premium is greater for women than for men. Furthermore, the union wage premium is more beneficial for women in the public sector compared to the private sector. The gender disparity in endowment return effect among non-union members is the primary factor contributing to the formation of the gender wage gap in both public and private sectors, with the effect being more pronounced in the public sector. Additionally, the gender disparity in unionism reduces the gender wage gap in the public sector while widening the wage gap in the private sector.
Keywords: 330; discrimination; Gender wage gap; public and private sector; unionism